Realizing Women's Potential in Agri-Food Systems - Vemireddy, Vidya; Puskur, Ranjitha (CGIAR GENDER Impact Platform, 2024)
A stakeholder dialogue on “Realizing Women’s Potential in Agri-Food Systems’ was organized by the Indian Institute of Management, Ahmedabad (IIMA) in collaboration with CGIAR GENDER Impact Platform and International Rice Research Institute on September 19, 2024. Experts across academia, civil society and international organizations working at the intersection of agri-food systems and gender were invited to participate in the discussions, which were helmed by Dr Vidya Vemireddy, Assistant Professor at IIMA and Dr Ranjitha Puskur, Lead, Evidence Module, CGIAR GENDER Impact Platform.